Accessing cancer services in North West England: the Chinese population. (7th January 2014) - Conway, A.M.; Clamp, A.R.; Hasan, J.; Goonetilleke, D.; Shore, K.; Wong, L.M.J.; Wong, J.; Jayson, G.
<x xml:space="preserve">Abstract</x> Relatively few Chinese patients access tertiary cancer services in North West England. We investigated the reasons behind this using a culturally sensitive questionnaire. The questionnaire, completed by 214 Chinese people in English, Cantonese or Mandarin, evaluated the Chinese population's access and satisfaction with primary care, understanding of cancer and awareness of local cancer services. Ninety‐five per cent of respondents were registered with a general practitioner (GP) and 75% had accessed primary care in the last year. Satisfaction with GP consultations was high but a third of respondents reported a lack of confidence in local National Health Service (NHS) services. Only 57% of eligible women had attended cervical screening programmes. The overall understanding of the causes and treatment of cancer and cancer services in the North West was poor. Despite registration with primary healthcare, the Chinese population under‐utilise cancer prevention programmes and tertiary cancer services because of a lack of awareness and understanding of cancer services in the North West. A significant proportion of the population is dissatisfied with the perceived slow service and lack confidence in services, with 41% considering using healthcare abroad. These data highlight the critical need to engage with, educate and support the Chinese population if they are to access NHS cancer services.